2018
DOI: 10.25259/ajs-7-2018
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Features of Diffuse Hashimoto Thyroiditis: Determining Sensitivity of Features and Predictors of Malignancy

Abstract: Objective The objective of this study was to determine the sensitivity and accuracy of five sonographic features of Hashimoto thyroiditis (HT) in histologically confirmed cases. In addition, to determine if sonographic features can serve as a predictor of underlying malignancy. Methods A cohort of 101 patients who underwent thyroidectomy for malignancy or other clinical conditions with histologically confirmed HT and a pre-operative thyroid ultrasound examination were included. A retrospective analysis of so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…All thyroid nodules were evaluated as previously described [18], and the background thyroid parenchyma was separately assessed. From the ultrasound report, HT was considered present if a diffusely heterogeneous parenchyma or the presence of HT was reported [19]. Clinical evaluation typically included a full medical history and physical examination, and assessment of serum TSH level.…”
Section: Methodsmentioning
confidence: 99%
“…All thyroid nodules were evaluated as previously described [18], and the background thyroid parenchyma was separately assessed. From the ultrasound report, HT was considered present if a diffusely heterogeneous parenchyma or the presence of HT was reported [19]. Clinical evaluation typically included a full medical history and physical examination, and assessment of serum TSH level.…”
Section: Methodsmentioning
confidence: 99%
“…All patients underwent sonographic and clinical assessment. From the ultrasound report, HT was considered present if the background parenchyma was diffusely heterogeneous or the presence of HT was reported (4). Serum TPOAb levels were measured (n = 2551 patients) when the serum TSH level was elevated or at the discretion of the clinician.…”
Section: Methodsmentioning
confidence: 99%
“…[30] Furthermore, in the current study, coarse echotexture as a sign of HT had a sensitivity of 81.54%, a result similar to those of Patel et al , who found that diffuse heterogeneity had a sensitivity of 88.2% in the diagnosis of HT. [31]…”
Section: Discussionmentioning
confidence: 99%